The complete mitochondrial genome of Channa argus, Channa maculata and hybrid snakehead fish [Channa maculata (♀) × Channa argus (♂)]. (June 2013) - Zhu, Shu-Ren; Ma, Ke-Yi; Xing, Zhi-Jun; Xie, Nan; Wang, Yu-Xi; Wang, Qun; Li, Jia-Le
Abstract : We sequenced and characterized the complete mitochondrial genome of Channa argus, Channa maculata and their hybrid [ C. maculata (♀) and C. argus (♂)]. All the three mitochondrial genomes contained the typical complement of 13 protein-coding genes, 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs) and 1 control region. The entire mitochondrial DNA (mtDNA) molecule of C. maculata was 16, 559 bp long while the complete mtDNA molecule of C. argus and hybrid snakehead fish was 16, 558 bp long. This is the first report on the complete mitogenome sequence of C. maculata and hybrid snakehead fish.